Programação Linear: da teoria à aplicação em sala de aula - Freitas, Erika Cristina de (2021)
This work aims to study Linear Programming problems. Therefore, we will investigate what these types of problems are, we will bring examples of how to model such problems, we will show how it is possible to determine the solution of these problems in R² and R³ geometrically, we will present how the Simplex algorithm works to solve problems of this type, including all the necessary theoretical foundation, and we will report an application of these problems in a high school classroom.